THE EFFECT OF INTERACTIVE MAD LIBS ACTIVITIES ON VOCABULARY MASTERY OF 8 th GRADERS IN UPT SPF SMP NEGERI 40 MAKASSAR - Rahmadani; Ratu Yulianti Natsir; Mallombassi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of Interactive Mad Libs Activities onimproving students' vocabulary mastery in English learning. The research wasconducted at UPT SPF SMP Negeri 40 Makassar with the subject of class VIIIstudents. This study used a pre-experimental design with one group pre-test andpost-test. The instrument used was a vocabulary multiple choice test of 20questions given before and after treatment. The treatment was conducted in fourmeetings through Interactive Mad Libs Activities with contextual stories thatrequired students to fill in the blanks according to certain word classes such asnouns, verbs, and adjectives. The data from the pre-test and post-test wereanalyzed quantitatively using SPSS, including the calculation of the mean value,standard deviation, and paired sample t-test. The results showed a significantincrease in students' vocabulary mastery, with an average pre-test score of 51.29increasing to 81.14 in the post-test. The paired sample t-test results showed asignificance value of 0.000 < 0.05 which means there is a significant differencebetween the pre-test and post-test scores. The findings prove that Interactive MadLibs Activities is effective in helping students learn, remember, and use vocabularyin a fun and meaningful context, and can be used as an alternative interactive andengaging English vocabulary learning strategy.